Unamendable Provisions in The 1945 Constitution to Limit The Power of Constitutional Amendment in Indonesia - Ilham Azhari; Dodi Haryono; Dessy Artina (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2024)
The concept of unamendable provisions in the 1945 Constitution of the Republic of Indonesia is an effort to limit the power of constitutional amendments to ensure they remain constitutional. In Indonesia, amendments to the 1945 Constitution are introduced through a highly stringent process, with certain provisions explicitly prohibited from being altered. These provisions aim to protect the fundamental aspects of the constitution, such as the unitary state form and the republican system of government, as stipulated in Article 37, paragraph 5 of the 1945 Constitution. This article examines whether the concept of unamendable provisions can be applied to other provisions not explicitly mentioned within the amendment limits.This research article employs a doctrinal legal approach using historical and conceptual methods, combined with descriptive analysis. Through this approach, the research explores the historical background of unamendable provisions and how this concept is applied in Indonesian legal practice. The findings indicate that, although not explicitly stated in the 1945 Constitution, certain provisions can be considered unamendable constructively, as they are closely related to the fundamental principles underlying the state and government of Indonesia, including provisions on the limitation of the presidential term of office. Unamendable provisions in the 1945 Constitution play a crucial role in maintaining the stability and continuity of the state and in preventing constitutional changes that could undermine the agreed-upon fundamental principles. This underscores the importance of understanding and interpreting these provisions